Gas Chromatographic Separation of Isomeric Phenols by Schiff`s Base Liquid Crystalline Stationary Phases - Hammza, Rana A (Al-Nahrain Journal of Science, 2013)
Abstract:The chromatographic behaviour of liquid crystalline compounds 4-(propyloxybenzylidene)-4`-p-aminoazobenzene (1) and 4-(butyloxybenz--ylidene)-4`-p-aminoazobenzene (2) as stationary phases for the separation of cresol isomers was investigated. These isomers were analysed on 4-(propyloxybenzylidene)-4`-p-aminoazobenzene within a nematic range of 142- 153° C with a temperature interval of 5° C. Better peak resolution was at a column temperature of 147° C. The analysis was repeated on a and 4-(butyloxybenzylidene)-4`-p-aminoazobenzene column at a nematic temperature of 176° C, which represented the end of the nematic range, and gave the optimum peak resolution. It was found that isomer better separation was obtained at 20% loading for both liquid crystal materials. Other columns of different liquid crystalline percentages (15% and 25%) were used. A chromatogram with unoverlapped peaks was only obtained in both cases at 20% column loading. The order of elution isomers under the applied chromatographic conditions is discussed. The separation of these isomers is also discussed on the basis of stereo chemical conformations.